2022
DOI: 10.1021/acs.iecr.2c00285
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Metallic Nanostructures for Biomedical Applications, Catalysis, and Beyond

Abstract: Nature has inspired scientists to develop green and sustainable nanomaterials with biomimetic functions. Particularly, biomimetic metallic nanostructures (biometal NPs) with unique optical, catalytic, and electrical properties have received tremendous attention in many fields, ranging from healthcare and agriculture to energy and environmental sciences. Biometal NPs synthesized by various natural resources such as plant extracts, biomolecules, bacteria, and even viruses possess unique biomimetic functions incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(14 citation statements)
references
References 478 publications
(805 reference statements)
0
14
0
Order By: Relevance
“…Plants are the most commonly used biological substrates for the green synthesis of NPs because they are biocompatible and readily available [55,56]. It is possible to reduce and stabilise ions using a combination of biomolecules such as proteins, amino acids, flavonoids, citric acid, various enzymes, polysaccharides, phenols, saponins, terpenoids and vitamins found in plants extracts [57][58][59][60].…”
Section: Bio-templates-mediated Synthesis Strategies 21 Plant Extractsmentioning
confidence: 99%
“…Plants are the most commonly used biological substrates for the green synthesis of NPs because they are biocompatible and readily available [55,56]. It is possible to reduce and stabilise ions using a combination of biomolecules such as proteins, amino acids, flavonoids, citric acid, various enzymes, polysaccharides, phenols, saponins, terpenoids and vitamins found in plants extracts [57][58][59][60].…”
Section: Bio-templates-mediated Synthesis Strategies 21 Plant Extractsmentioning
confidence: 99%
“…31 In another example, the AIE approach was achieved by changing pH (3.0 to 6.1) and subsequently by 5 h boiling, leading to highly fluorescent GSH-AgNCs with a core−shell Ag(0)@ Ag(I)−thiolate nanostructure and three species, Ag 10 SG 6 , Ag 10 SG 5 , and Ag 11 SG 7. 45 In this study, GSH-AgNCs were obtained with different sizes, while well-defined size GSH-AuNCs with high purity (Au 15 (SG) 13 ) could be achieved in a controlled kinetic reduction reaction at pH ∼ 2 together with the addition of borane tert-butylamine (TBAB) as a relatively weak reducing agent. 46 Moreover, the pH-controlled CO reduction approach causes GSH-AuNCs with well-defined sizes so that four discrete sizes of Au 10−12 , Au 15 , Au 18 , and Au 25 were obtained by adjusting the pH to 7.0, 9.0, 10.0, and 11.0, respectively, at a mole ratio of 2GSH/1HAuCl 4 at room temperature.…”
Section: Synthesis Mechanismmentioning
confidence: 99%
“…Moreover, they generally have a ligand shell and a metal core (i.e., Au, Ag, Pt, Cu) . Numerous investigations have demonstrated that the fluorescence of metal NCs is sensitive to changes in the microenvironment caused by changes in the electron-transferring mechanism between the metal core and the protected ligand . Several nanoplatforms based on fluorescence metal nanoclusters (FMNCs) have been developed for colorimetric assays because of their high water solubility, good biocompatibility, and rich surface chemistry for conjugation .…”
Section: Introductionmentioning
confidence: 99%
“…Less rigorous and sustainable methodologies are critical for engineering advanced metal–polymer nanostructures with applications in energy storage and electronics; accordingly, it is necessary to combine separation and advanced analytical techniques for reliable characterizations of the inherent molecular heterogeneities. , Metallic nanostructures have multiple applications in energy storage, biosensors, drug delivery, wearable electronics, and robotics, to mention just a few. , However, these metallic nanostructures are inherently complex and heterogeneous, with multiple distributions in their molecular properties . As such, combinations of separation and advanced analytical techniques are prerequisites for the reliable definition, understanding, and fine-tuning of the fundamental nexus between (i) inherent molecular properties, (ii) physicochemical properties and multiple functionalities, and (iii) the pristine end-use applications …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Metallic nanostructures have multiple applications in energy storage, biosensors, drug delivery, wearable electronics, and robotics, to mention just a few. 3,4 However, these metallic nanostructures are inherently complex and heterogeneous, with multiple distributions in their molecular properties. 5 As such, combinations of separation and advanced analytical techniques are prerequisites for the reliable definition, understanding, and fine-tuning of the fundamental nexus between (i) inherent molecular properties, (ii) physicochemical properties and multiple functionalities, and (iii) the pristine end-use applications.…”
Section: ■ Introductionmentioning
confidence: 99%